Identifying Youth at Risk for Commercial Sexual Exploitation Within Child Advocacy Centers: A Statewide Pilot Study. Issue 5 (March 2021) - Brandt, Tiffany West; Lind, Teresa; Schreier, Alayna; Sievers, Chad M.; Kramer, Teresa L.
Commercial sexual exploitation of children (CSEC) is a social problem in the United States that has recently received growing attention from policy makers, advocates, and researchers. Despite increasing awareness of this issue, information on the prevalence, demographic profile, and psychosocial needs of victims of CSEC is scarce. To better understand the scope of CSEC and to examine the feasibility of screening for CSEC in Child Advocacy Centers (CACs), a pilot study was initiated through Arkansas Building Effective Services for Trauma (ARBEST) to identify youth who may be at risk for commercial sexual exploitation. Data for this pilot study were collected from all of the state's CACs ( n = 14) over a 6-month period. Family advocates completed a screening questionnaire adapted from Greenbaum, Dodd, and McCracken with 918 youth aged 12 to 18 years old treated at CACs. Almost 20% of youth were identified as being at high risk for experiencing CSEC. Furthermore, youth classified as high-risk for commercial sexual exploitation reported significantly more avoidance symptoms on the UCLA (University of California at Los Angeles) PTSD (Posttraumatic Stress Disorder) Reaction Index than youth classified as low-risk. The results suggest that a significant portion of youth treated at CACs in Arkansas are at high risk for experiencing commercial sexual exploitation, which may be associated with a particular pattern of trauma symptoms. These findings also lend support for the feasibility and utilization of a screening questionnaire as part of routine care in CACs to potentially identify youth at risk for CSEC.